Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Pegawai Kantor Puskesmas Rengas Pulau - Arkan, Muhammad; Supriadi, Supriadi; Tahir, M.; Bakhtiar, Bakhtiar; Wahyuni, Neni Sri (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
Abstract is written The formulation of this research is how leadership and motivation influence the performance of employees at the Rengas Pulau Community Health Center. The purpose of this research is to determine and analyze the influence of leadership and motivation on the performance of employees at the Rengas Pulau Community Health Center. This research is a quantitative descriptive study. Data collection techniques were conducted through interviews, questionnaires, and documentation studies. The sample in this study was 43 people. Variables were measured using a Likert scale. Hypothesis testing used multiple linear regression analysis through the F test and t test. The results of the simultaneous test showed a very significant impact on employee performance at the Rengas Pulau Community Health Center. It can be explained that leadership influences employee performance, and motivation influences employee performance. Both leadership and motivation influence employee performance.